2018
DOI: 10.1007/s12127-018-0234-2
|View full text |Cite
|
Sign up to set email alerts
|

Acetone and perdeuterated acetone in UV-IMS

Abstract: Measuring a mixture of acetone and perdeuterated acetone (acetone-d6) with an ultra-high resolution drift time ion mobility spectrometer (resolving power of Rp = 235) and ultraviolet ionization (10.6 eV) at ambient pressure reveals three separated peaks. Two of the peaks can easily be associated with acetone and perdeuterated acetone. In a former publication several findings indicated an exchange of a methyl group and the formation of a H3COCD3 related peak. In this work the formed ion species were analyzed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…The reduced ion mobilities ( K 0 ) of the acetone monomer and dimer were 1.88 and 1.84 cm 2 V –1 s –1 , respectively (obtained from the result shown in Figure S10). These values are compared with three references: reference 1 (monomer, 1.91 cm 2 V –1 s –1 and dimer, 1.79 cm 2 V –1 s –1 ); reference 2 (dimer, 1.89 cm 2 V –1 s –1 ); and reference 3 (dimer, 1.85 cm 2 V –1 s –1 ) . The differences between the experimental and literature values may be due to the differences in the type of drift gas and its flow rate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced ion mobilities ( K 0 ) of the acetone monomer and dimer were 1.88 and 1.84 cm 2 V –1 s –1 , respectively (obtained from the result shown in Figure S10). These values are compared with three references: reference 1 (monomer, 1.91 cm 2 V –1 s –1 and dimer, 1.79 cm 2 V –1 s –1 ); reference 2 (dimer, 1.89 cm 2 V –1 s –1 ); and reference 3 (dimer, 1.85 cm 2 V –1 s –1 ) . The differences between the experimental and literature values may be due to the differences in the type of drift gas and its flow rate.…”
Section: Resultsmentioning
confidence: 99%
“…These values are compared with three references: reference 1 (monomer, 1.91 cm 2 V –1 s –1 and dimer, 1.79 cm 2 V –1 s –1 ); reference 2 (dimer, 1.89 cm 2 V –1 s –1 ); and reference 3 (dimer, 1.85 cm 2 V –1 s –1 ) . The differences between the experimental and literature values may be due to the differences in the type of drift gas and its flow rate. The peak at the drift time ( t d ) of 6.95 ms is attributed to reactant ion peak RIP-1 [ammonium ion (NH 4 + (H 2 O) n )] and the one at t d = 7.57 to RIP-2 [hydronium ion (H + (H 2 O) n )]…”
Section: Resultsmentioning
confidence: 99%
“…A scientific basis for realizing the first coupling of chip-HPLC and IMS is previous works by the Belder group on chip-HPLC/MS ,,,,, and the Zimmermann group on the development of high-resolution IMS systems. ,,,, As both approaches utilized ESI, a marriage of both systems initially seemed easily applicable. However, first attempts to couple HPLC glass chips with an integrated electrospray emitter to the previously developed ESI-IMS system revealed that the practical realization was challenging.…”
Section: Resultsmentioning
confidence: 99%
“…Introduced by Karasek in the early 1970s, ion mobility spectrometry (IMS) is a well-established analytical technique and has been a routine analysis tool for decades. Key features of IMS are its low system complexity and thus its compact design and low cost, , operation at ambient pressures, as well as the ability to separate ions in the gas phase based on their charge, size, and shape. Common applications of IMS are the analysis of gases, explosive vapors, chemical warfare agents, and other toxic volatiles. ,, As evident from the literature, the technology is currently experiencing a scientific renaissance. The combination of IMS with electrospray ionization-mass spectrometry (ESI-MS) and the availability of respective commercial products has further increased the interest in the technology. , While IMS separates gas phase ions in a split second, the recent advent of lab-on-a-chip technology has led to devices capable of separating compounds in liquid phase at high speed. …”
mentioning
confidence: 99%
See 1 more Smart Citation